2019
DOI: 10.1071/sh19001
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for behavioural interventions addressing condom use fit and feel issues to improve condom use: a systematic review

Abstract: Continuing high rates of sexually transmissible infections (STIs) in many countries highlight the need to identify effective behavioural interventions. Consistent and correct use of male condoms is a key strategy for the prevention of STIs. However, some men report problems with condom fit (e.g. the size and shape of the condom) and feel (e.g. tightness, irritation, sensitivity), which inhibits their use. We conducted a systematic review to identify existing interventions addressing condom use fit and feel pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
0
7
0
3
Order By: Relevance
“…These values could be due to the psychological attribution of condom use rather than the barriers to condom use. This is expected, as CAEP expectations are reported even among young people who have never used condoms ( Morales et al., 2019 ; Vallejo-Medina et al., 2020 ), and have decreased after implementing health promotion programs ( Anstee et al., 2019 ). Indeed, CAEP could be related to a negative attitude toward condom use with respect to pleasure ( Plaza-Vidal et al., 2020 ).…”
Section: Discussionmentioning
confidence: 88%
“…These values could be due to the psychological attribution of condom use rather than the barriers to condom use. This is expected, as CAEP expectations are reported even among young people who have never used condoms ( Morales et al., 2019 ; Vallejo-Medina et al., 2020 ), and have decreased after implementing health promotion programs ( Anstee et al., 2019 ). Indeed, CAEP could be related to a negative attitude toward condom use with respect to pleasure ( Plaza-Vidal et al., 2020 ).…”
Section: Discussionmentioning
confidence: 88%
“…Many interventions to date have failed to consider the promotion of pleasurable condom use and to address issues around the fit and feel of condoms, including condom size, texture, and thickness. One review found only 5 studies (out of the 123 condom promotion studies identified) focused on improving fit and feel [ 14 ], despite its positive association with use [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there have been attempts to use health psychology in the design of sexual health interventions. These have included behavioural interventions to improve condom use (Anstee et al, 2019 ; Stone et al, 2018 ); to enhance chlamydia testing (McDonagh et al, 2018 , 2020 ); to promote HIV medication adherence (Spaan et al, 2020 ); to promote HIV testing (Flowers et al, 2019 ). There has been relatively less research on enhancing sexual health services.…”
Section: Introductionmentioning
confidence: 99%